Real-Time MRI–Guided Stereotactic Aspiration of Spontaneous Intracerebral Hematoma: A Preclinical Feasibility Study. Issue 2 (February 2022) - Patra, Devi P.; Welz, Matthew E.; Turcotte, Evelyn L.; Pandey, Rajesh; Vij, Kamal; Daly, Max; Rabon, Matthew; Korszen, Stephanie; Zhou, Yuxiang; Halpin, Brooke; Marchese, Marco L.; Syal, Arjun; et al.
Abstract : BACKGROUND: Minimally invasive surgical techniques have reinvigorated the role of surgical options for spontaneous intracranial hematomas; however, they are limited by the lack of real-time feedback on the extent of hematoma evacuation. OBJECTIVE: To describe the development of a MRI-guided catheter-based aspiration system, the ClearPoint Pursuit Neuroaspiration Device (ClearPoint Neuro) and validation in phantom models. METHODS: In this preclinical experimental trial, 8 phantom brains with skull models were created to simulate an intracranial hematoma with 2 clot sizes, 30 cc (small clot) and 60 cc (large clot). After registration, the aspiration catheter (Pursuit device) was aligned to the desired planned trajectory. The aspiration of the clot was performed under real-time MRI scan in 3 orthogonal views. The primary end point was reduction of the clot volume to less than 15 cc or 70% of the original clot volume. RESULTS: Successful completion of clot evacuation was achieved in all models. The average postaspiration clot volume was 9.5 cc (8.7 cc for small clots and 10.2 cc for large clots). The average percentage reduction of clot volume was 76.3% (range 58.7%-85.2%). The average total procedure time (from frame registration to final postaspiration clot assessment) was 50 min. The average aspiration time was 6.9 min. CONCLUSION: This preclinical trial confirms the feasibility and efficacy of MRI-guided aspiration under real-time image guidance in simulation models for intracranial hematoma. Clinical use of the system in patients would further validate its efficacy and safety.